First Case Report of Turcot Syndrome Type 1 in Colombia. (18th December 2012) - Dora, Vallejo; Diego, Garnica; Rómulo, Bonilla; Natalia, Olaya
Abstract : Turcot syndrome is an autosomal recessive disorder clinically characterized by the occurrence of primary tumors of the central nervous system and adenomatous colonic polyps during the first or second decades of life, with a spectrum of clinical features such as "café-au-lait" spots, axillary freckling, and hyperpigmented spots. Currently its prevalence globally and in Colombia remains unknown. We present the case of a 20-year-old male with a clinical presentation of both glioblastoma multiforme and multiple adenomatous colonic polyps. The molecular genetics study revealed a mutation in Kras Asp12 gene and altered expression of HMSH2 and HMSH6 proteins encoded by the DNA mismatch repair genes in two of the colonic polyps. Even though this clinical presentation may suggest a shorter survival rate, this patient is still alive after seven months of treatment. A literature review complements this report.